Технология ванадийсодержащих ферросплавов - Зайко В. П. Виктор Петрович; Жучков В. И. Владимир Иванович; Леонтьев Л. И. Леопольд Игоревич; Карноухов В. Н. Владимир Николаевич; Воронов Ю. И. Юрий Иванович (Москва, Академкнига, 2004)
Авт. указаны на обороте тит. л.